CARA-CARA NICA MEMPENGARUHI RAKYAT SUPAYA TIDAK BERSIMPATI KEPADA PARA PEJUANG PADA MASA REVOLUSI FISIK DI BALI 1945-1950 - Ida Bagus Astika Pidada (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2019)
[Title: The Ways of Influencing the People of NICA to Understand at Physical Revolution for Balinese People in Bali 1945-1950] Giving up without the conditions of Lieutenant General H. Ter Pooerten (Commander of the Dutch East Indies) to Lieutenant General Hitosyi Imamura (Japanese Army Chief), then the Dutch East Indies government has since ended in Indonesia. Not a long time ago Japan ruled in Indonesia, on August 15th, 1945 surrendered unconditionally to the allies. Then on March 2nd, 1946 the Y Brigade began landed along the Sanur coast. This Y Brigade is nicknamed "Gajah Merah". The arrival of the Gajah Merah in Bali, the situation became unsafe. The arrival of the Dutch (NICA) received resistance from fighters in Bali under the leadership of Lieutenant Colonel I Gusti Ngurah Rai. Sympathy getting from the Dutch people use various ways of influencing. The Dutch (NICA) influences the people in two ways, namely by means of soft and violent methods. In the soft way the Dutch (NICA) gave material to the people such as: giving cigarettes, snacks, money, batik cloth, rice and traveling by car. In providing soft assistance the Dutch also use their accomplices such as: NICA Gandek, AP and others. The Netherlands (NICA) in this case looks good and generous to the people so they get sympathy. Generally, it is influenced by the Dutch, whose economies are poor and whose education is low. By means of violence, the Dutch deliberately exhibited fighters who were captured by the public such as being kicked, beaten, dragged by car, and shot in front of the people. This method is carried out to regions that are pro-republic so that people become deterred and afraid. In this way the Dutch (NICA) hopes that the people will no longer want to help the fighters. To fall on the mentality of the Dutch people (NICA) deliberately stripped their hands or soldiers who were killed in a war that was paraded around the city by using an open truck that was rumored to be a young man who was killed. The mothers and fathers who were provoked by the Dutch propaganda, his soul was shaken. This is the way the Dutch influenced the Balinese people, however, the Balinese people and fighters were not deterred. Evidently the people and fighters remain united so that the physical revolution that took place in Bali can last long enough.